Strategies of brain-based learning theory and its impact on the achievement of students of the Department of Art Education in Teaching Methods (Al-Academy, 2022)
The aim of the current research is to reveal the effect of using brain-based learning theory strategies on the achievement of Art Education students in the subject of Teaching Methods. The experimental design with two equal experimental and control groups was used. The experimental design with two independent and equal groups was used, and the total of the research sample was (60) male and female students, (30) male and female students represented the experimental group, and (30) male and female students represented the control group. The researcher prepared the research tool represented by the cognitive achievement test consisting of (20) questions, and it was characterized by honesty and reliability, and the experiment lasted (6) weeks and after applying the tool and using statistical means in data processing. The results showed that there were statistically significant differences at the level of significance (0.05) between the average scores of the experimental group students who studied according to study plans based on brain-based learning and the average scores of the experimental group students who studied according to the usual method in their answers to paragraphs Postgraduate cognitive achievement test.  The superiority of the students of the experimental group who used the study plans designed according to the strategies of the theory of brain-based learning as a strategy (KWL) had a positive impact on the cognitive achievement of this group and their superiority over their peers the students of the control group who used the usual method